Insects and Bobwhite Quail Brood Habitat Management - George A. Hurst (National Quail Symposium Proceedings, 2017)
Small insects were the most important foods eaten by quail chicks 2 to 20 days of age. The foods eaten, in order of importance, were beetles, leafhoppers, true bugs, spiders, grasshoppers, ants, larvae, snails, and flies. Important seeds ingested were Panicum spp., Carex spp., Scleria spp., Paspalum spp., and Setaria sp. The effect of fire, a major tool in southern quail management, on insect populations was studied by sampling burned and unburned plots with a sweep net and a D-vac machine. On an old-field type of habitat, population densities and biomass of herbivorous insect populations were significantly greater on February-burned plots than on 5-year-old unburned plots. Two peaks in numbers of insects were found. The first peak of ca. 64,000/acre (sweep net) occurred in mid-June. The second peak occurred in mid-August (D-vac) with a density 0f ca. 90,000/acre. Total insect biqmass, excluding individuals over 0.035 g dry weight, averaged 147 g/acre (sweep net) and 128 g/acre (D-vac). In the second phase of the study, in a longleaf pine forest habitat, grasshoppers were the only species of insect having significantly greater density and biomass on unburned, 3-year-old "roughs" than on annually burned plots. Lack of litter on annually burned plots probably caused this disparity. At peak density, in the period of mid-July to early August, sweep-net density was 19,500/acre and D-vac density was 58,500/acre. Total insect biomass averaged 79 g/acre (sweep net) and 52 g/acre (D-vac). The major considerations for brood habitat are abundance and availability of insects. In old-field habitat, fire increases insect abundance and removes accumulated litter, opening the area for ease of chick movement. If the soil is fertile, then annual burns are feasible. The interval of burning advocated is 1 or 2 years, but local problems may modify this. Burning annually in the poor-soil region of the longleaf forest type is not necessary.